Persepsi Kelompok Minoritas (kristen) terhadap Kelompok Mayoritas (islam) terkait Sikap Toleransi Beragama di Desa Karangbener - Mohammad Khasan; Anton Kristianto; Ida Yuliyani; Ika Yuniana; Umar Faiz; Alfian Khoirun Nizam (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2024)
This study aims to explore and describe the perceptions of minority groups towards the majority group regarding attitudes toward religious tolerance. A case study was condected in Karangbener Village, Bae District, Kudus Regency. Using descriptive qualitative research methods, the study involved semi-structured interviews for data collection, with analysis conducted through thematic analysis. Data was first coded and research credibility ensured via data source triangulation. Participants were selected based on their residency in Karangbener Village for at least 10 years and their status as minority group members, with a total of three participants. Findings revealed that all participants agreed the majority group in Karangbener Village showed good tolerance, living harmoniously without conflict and supporting each other during disasters or illnesses. They also reported feeling very happy and free from discrimination despite being in the minority. Additionally, the tolerance between religious communities in the village is described as excellent, evidenced by mutual assistance, cooperation, sharing, community service, greetings, and maintaining relationships during religious celebrations for both Islam and Christianity. Implications for promoting religious tolerance are also further discussed.